2020
DOI: 10.1016/j.bpj.2020.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Pore Formation Observed during SNARE-Mediated Vesicle Fusion with Pore-Spanning Membranes

Abstract: Planar pore-spanning membranes (PSMs) have been shown to be a versatile tool to resolve docking and elementary steps of the fusion process with single large unilamellar vesicles (LUVs). However, in previous studies, we monitored only lipid mixing and did not gather information about the formation of fusion pores. To address this important step of the fusion process, we entrapped sulforhodamine B at self-quenching concentrations into LUVs containing the v-SNARE synaptobrevin 2, which were docked and fused with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…From the mean square displacements, a mean diffusion coefficient of 0.42 ± 0.15 μm 2 /s was calculated. (Mühlenbrock et al 2020) Compared to the diffusion constant of syntaxin 1A in the f-PSM, the diffusion coefficient of the docked vesicles is by a factor of five smaller. A close contact between vesicle and membrane and the displacement of the intermembrane water layer as well as multiple interacting SNARE-complexes might be responsible for the reduced diffusion coefficient compared to that of a single SNARE.…”
Section: Single Vesicle Fusion With F-psmsmentioning
confidence: 95%
See 4 more Smart Citations
“…From the mean square displacements, a mean diffusion coefficient of 0.42 ± 0.15 μm 2 /s was calculated. (Mühlenbrock et al 2020) Compared to the diffusion constant of syntaxin 1A in the f-PSM, the diffusion coefficient of the docked vesicles is by a factor of five smaller. A close contact between vesicle and membrane and the displacement of the intermembrane water layer as well as multiple interacting SNARE-complexes might be responsible for the reduced diffusion coefficient compared to that of a single SNARE.…”
Section: Single Vesicle Fusion With F-psmsmentioning
confidence: 95%
“…In the centre of the pore, the PSMs are flat presumably as they experience a certain pre-stress in the mN/m-range (Janshoff and Steinem 2015 ; Kocun et al 2011 ; Kuhlmann et al 2014 ). It is well conceivable that this membrane geometry, as well as the broad distribution of the ΔN49 complex concentration in the individual GUVs (Mühlenbrock et al 2020 ) influence the observed differences in the protein distribution.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations